Nationalism, Chauvinism and Racism as Reflected in European Musical Thought and in Compositions from the Interwar Period - Tuchowski, Andrzej (2019)
This book concerns the ways in which many different types of nationalism, chauvinism and racism penetrated into musical thought in the interwar period, and how the leading artistic personalities of that period reacted to these ideologies. The concept of "nationalism" is understood broadly in this book and covers the entire spectrum of its positive and negative aspects. The topics listed in the book’s title have been discussed on the example of selected four countries, significant with respect to population and territory and representing different social-political systems: Germany (mostly after 1933), Italy, Poland (after 1926) and Great Britain. This selection is also representative of the main ethnic groups in Europe: Anglo-Saxon, Germanic, Latin-Romance and Slavic.